Anti-aging viscosity-reducing adhesive composition and application thereof in power-on viscosity-reducing adhesive tape

By combining modified acrylic resin with organosilicon and hydroxyl-terminated polybutadiene, an aging-resistant and anti-adhesive composition is formed, which solves the problems of adhesion and flame retardancy of electrically conductive anti-adhesive tape in extreme environments, and achieves stable adhesion under high temperature and humidity and thermal shock, as well as easy peeling after being electrically applied.

CN120904828APending Publication Date: 2025-11-07DONGGUAN SEUNGHO NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511276085.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing electrostatically conductive adhesive tapes are flammable in smart electronic products and new energy battery packs, and their adhesion and electrostatically conductive adhesive properties decrease after aging in extreme environments, making it difficult to meet the requirements for aging resistance and flame retardancy.

Method used

A modified acrylic resin is formed by combining modified acrylic resin with organosilicon and hydroxyl-terminated polybutadiene. By introducing a triazine ring structure and hydrosilylation grafting vinyl silicone oil, a modified acrylic resin is formed, which enhances the thermal stability, water resistance and flame retardancy of the adhesive composition. Furthermore, the high-temperature aging resistance is improved by forming a polyurethane-acrylic interpenetrating network with hydroxyl-terminated polybutadiene through HDI trimer.

Benefits of technology

Under high temperature and humidity and thermal shock, the modified acrylic resin composition can still maintain good adhesion and ultra-low viscosity after energization, avoid residue, and has excellent aging resistance and flame retardant properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of viscosity-reducing adhesives, and discloses an anti-aging viscosity-reducing adhesive composition and application thereof in an electrified viscosity-reducing adhesive tape, the anti-aging viscosity-reducing adhesive composition comprises modified acrylic resin, tackifying resin, ionic liquid, an ion channel auxiliary agent, an HDI tripolymer, hydroxyl-terminated polybutadiene and ethyl acetate; modified hydroxyethyl acrylate in the modified acrylic resin is prepared by respectively reacting isophorone diisocyanate with a monohydroxy s-triazine derivative and hydroxyethyl acrylate; according to the monohydroxy s-triazine derivative, cyanuric chloride reacts with m-xylene and resorcinol to synthesize a dihydroxy chlorine-containing s-triazine intermediate, then the dihydroxy chlorine-containing s-triazine intermediate and 1, 4-p-xylylene dichloride are subjected to substitution to prepare a reaction product, and the reaction product reacts with p-aminodiphenylamine and 3, 5-di-tert-butyl-4-hydroxybenzylamine at the same time to prepare the monohydroxy s-triazine derivative. The viscosity-reducing glue composition prepared by the invention has good thermal stability, water resistance, high-temperature aging resistance and flame-retardant effect, and can still maintain viscosity reduction after high-temperature, high-humidity and cold and hot impact aging.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of tack-reducing adhesives, and particularly relates to an aging-resistant tack-reducing adhesive composition and application thereof in an electrically conductive tack-reducing adhesive tape. BACKGROUND

[0002] The electrically conductive tack-reducing adhesive tape is a kind of adhesive tape that can effectively solve the pain points such as damage caused by traditional adhesives during disassembly, low efficiency, etc. in the medical and electronic industries, and can provide great convenience for the installation and fixing of smart electronic devices and new energy battery packs and the disassembly and recycling thereof.

[0003] The existing electrically conductive tack-reducing adhesive tape mainly relies on two mechanisms: one is to add an ionic liquid (such as a quaternary ammonium salt) in the adhesive layer, and after being electrified, the anion and the cation migrate to the electrodes, respectively, to cause an oxidation-reduction reaction, thereby destroying the interfacial bonding between the adhesive layer and the substrate; the other is to add a conductive agent (such as graphite) and a physical foaming agent (such as the Matsumoto microsphere) in the adhesive layer, and after being electrified, the electric current generates Joule heat to trigger the expansion of the foaming agent, thereby reducing the bonding area. In the method of adding an ionic liquid, the amount of the ionic liquid added usually needs to reach 30% to ensure the electrical conductivity, and a high amount of addition may cause precipitation. In addition, inorganic conductive fillers (such as graphite and nano-silver) are prone to agglomeration, which affects the uniformity of the adhesive layer and may result in incomplete tack reduction or residual glue.

[0004] In addition, when the existing electrically conductive tack-reducing adhesive tape is applied to smart electronic products and new energy battery packs, some extreme environments and long-term contact with air need to be considered, and the problem of aging caused by long-term contact with air also needs to be considered. In addition, the existing electrically conductive tack-reducing adhesive tape has the characteristic of being extremely flammable, and therefore, in actual application, higher requirements are put forward for the electrically conductive tack-reducing adhesive tape, and the electrically conductive tack-reducing adhesive tape needs to be modified to have flame retardancy, and after being subjected to extreme environmental impact and long-term environmental aging, the electrically conductive tack-reducing adhesive tape still needs to have good bonding and electrically conductive tack-reducing properties. SUMMARY

[0005] To solve the problems mentioned in the background, the purpose of the present application is to provide an aging-resistant tack-reducing adhesive composition and application thereof in an electrically conductive tack-reducing adhesive tape. The modified acrylic resin is used to endow the tack-reducing adhesive composition with good thermal stability, water resistance, high-temperature aging resistance and flame retardant effect. In addition, the introduction of the organic silicon and the hydroxyl-terminated polybutadiene can enable the tack-reducing adhesive composition to maintain the tack-reducing ability after being subjected to high-temperature and high-humidity aging and cold and hot impact aging.

[0006] The purpose of the present application can be achieved by the following technical solutions. An aging-resistant tack-reducing adhesive composition comprises the following components in parts by weight: modified acrylic resin 60-75 parts, tackifying resin 10-20 parts, ionic liquid 8-15 parts, ionic channel additive 3-6 parts, HDI trimer 1-3 parts, hydroxyl-terminated polybutadiene 15-20 parts and ethyl acetate 40-80 parts. The modified acrylic resin comprises the following components by weight: 40-70 parts of acrylic ester soft monomer, 10-20 parts of acrylic ester hard monomer, 5-10 parts of modified hydroxyethyl acrylate, 2-8 parts of acrylic acid, 5-10 parts of vinyl silicone oil, 0.2-1 part of initiator, 0.05-0.1 part of platinum catalyst, and 50-60 parts of solvent; The modified hydroxyethyl acrylate is prepared by using isophorone diisocyanate as a bridging agent to respectively undergo nucleophilic addition reactions with a monohydroxy s-triazine derivative and hydroxyethyl acrylate; The monohydroxy s-triazine derivative is prepared by using cyanuric chloride and m-xylene to synthesize a s-triazine intermediate through a Friedel-Crafts reaction, then performing a Friedel-Crafts reaction on the s-triazine intermediate with resorcinol to obtain a dihydroxy chlorine-containing s-triazine intermediate, then performing a substitution reaction on the dihydroxy chlorine-containing s-triazine intermediate with 1,4-p-dichlorobenzyl to obtain a monohydroxy-substituted chlorine-containing s-triazine intermediate, and then performing a substitution reaction on the monohydroxy-substituted chlorine-containing s-triazine intermediate with p-aminodiphenylamine and 3,5-di-tert-butyl-4-hydroxybenzylamine.

[0007] Preferably, the preparation method of the modified acrylic resin comprises the following steps: S1, weigh each component by weight parts, take the acrylic ester soft monomer, acrylic ester hard monomer, modified hydroxyethyl acrylate, acrylic acid, and solvent in a reaction kettle, and preheat at 55-65℃ under stirring for 0.5-1h; S2, heat the reaction kettle to 70-75℃, and take the acrylic ester soft monomer, acrylic ester hard monomer, modified hydroxyethyl acrylate, acrylic acid, solvent, and initiator into a metering tank, and complete the dropwise addition within 3h; S3, after the dropwise addition is completed, keep warm for 0.5-1h, then add platinum catalyst, vinyl silicone oil, and solvent into the metering tank, complete the dropwise addition within 1h, keep warm for 1-1.5h, then add initiator and solvent, complete the dropwise addition within 0.5h, keep warm for 1.5-2h, then cool down and discharge, to obtain the modified acrylic resin.

[0008] Preferably, the preparation method of the modified hydroxyethyl acrylate comprises the following steps: (1) add cyanuric chloride and chlorobenzene into a reactor, stir and mix, then add anhydrous aluminum chloride in batches under ice water bath, keep stirring and mixing under ice bath, then dropwise add m-xylene, keep ice bath reaction for 2-3h, after the reaction is completed, dropwise add hydrochloric acid into the reactor at room temperature, separate the organic layer, extract the water layer with chlorobenzene, combine the organic layers, dry with anhydrous sodium sulfate, rotary evaporate under vacuum, then filter, to obtain the s-triazine intermediate; (2) adding the s-triazine intermediate and chlorobenzene into the reactor, stirring and mixing, then adding anhydrous aluminum chloride in batches under ice water bath, stirring and mixing, then adding resorcinol, reacting at 75-80°C for 2-3h, adding hydrochloric acid into the reactor after the reaction is completed, recovering chlorobenzene water azeotrope through normal pressure distillation until the top temperature is 100°C, hot filtration, and recrystallizing the crude product with toluene to obtain the dihydroxy chloro-containing s-triazine intermediate; (3) adding the dihydroxy chloro-containing s-triazine intermediate, 1,4-p-dichlorobenzene and tetrahydrofuran into the reactor, stirring and mixing, then stirring and reacting at 65-75°C, adding triethylamine in batches during the reaction, reacting for 4-5h, and then filtering, rotary evaporation and drying to obtain the monohydroxy-substituted chloro-containing s-triazine intermediate; (4) adding the monohydroxy-substituted chloro-containing s-triazine intermediate and m-xylene into the reactor, stirring and mixing under ice water bath, then adding p-aminodiphenylamine and 3,5-di-tert-butyl-4-hydroxybenzylamine, stirring and reacting for 1-2h, then increasing the temperature to 40-60°C, adding sodium hydroxide, and continuously stirring and reacting for 5-7h, and then washing, filtering and drying to obtain the monohydroxy s-triazine derivative; (5) adding the monohydroxy s-triazine derivative and isophorone diisocyanate into the reactor, stirring and mixing, then adding dibutyltin dilaurate, stirring and reacting at 35-45°C for 1-2h, then adding hydroxyethyl acrylate, continuously stirring and reacting at 45-55°C for 1-2h, and then filtering, rotary evaporation and drying to obtain the modified hydroxyethyl acrylate.

[0009] Preferably, the molar ratio of cyanuric chloride to m-xylene in the step (1) is 1:1-1.1; and the molar ratio of the s-triazine intermediate to resorcinol in the step (2) is 1:1-1.1.

[0010] Preferably, the molar ratio of the dihydroxy chloro-containing s-triazine intermediate to 1,4-p-dichlorobenzene in the step (3) is 1:1-1.1; and the molar ratio of the monohydroxy-substituted chloro-containing s-triazine intermediate, p-aminodiphenylamine and 3,5-di-tert-butyl-4-hydroxybenzylamine in the step (4) is 1:1-1.1:1-1.1.

[0011] Preferably, the molar ratio of the monohydroxy s-triazine derivative, isophorone diisocyanate and hydroxyethyl acrylate in the step (5) is 1:1-1.1:1-1.2.

[0012] Preferably, the acrylate soft monomer comprises at least one of ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, lauryl acrylate and stearyl acrylate; and the acrylate hard monomer comprises at least one of methyl methacrylate, tert-butyl acrylate and cyclohexyl acrylate.

[0013] Preferably, the molecular weight of the vinyl silicone oil is 500-1000; the Pt concentration in the platinum catalyst is 3000 ppm; the initiator is at least one of azobisisobutyronitrile and dibenzoyl peroxide; and the solvent is a mixed solvent of toluene and ethyl acetate.

[0014] Preferably, the tackifying resin is at least one of terpene resin, terpene phenolic resin, hydrogenated terpene resin, C5 / C9 petroleum resin, and rosin resin; the ionic liquid is at least one of imidazole, pyridine, quaternary ammonium, quaternary phosphonium, pyrrolidine, and piperidine; and the ionic channel assistant is at least one of low-molecular-weight polyethylene glycol, gamma-butyrolactone, 1,3-dioxolane, N-methylpyrrolidone, and propylene glycol methyl ether.

[0015] The application of the anti-aging tack-reducing adhesive composition in an electrically conductive tack-reducing adhesive tape includes the following steps: weighing each component, stirring and mixing the modified acrylic resin, the tackifying resin, the ionic liquid, the ionic channel assistant, the HDI trimer, the hydroxyl-terminated polybutadiene, and the ethyl acetate uniformly, coating the mixture on the aluminum foil surface of the composite aluminum foil substrate in a coating manner, drying, and then adhering a silicone release film to obtain the electrically conductive tack-reducing adhesive tape.

[0016] The application has the following advantages: The application utilizes cyanuric chloride and m-xylene to synthesize a s-triazine intermediate through a Friedel-Crafts reaction, then utilizes resorcinol and the s-triazine intermediate to perform a Friedel-Crafts reaction to obtain a dihydroxy chloro-s-triazine intermediate with one remaining chlorine atom, then utilizes the substitution reaction between one chlorine atom in 1,4-p-dichlorobenzyl and one hydroxyl group in the dihydroxy chloro-s-triazine intermediate to obtain a monohydroxy-substituted chloro-s-triazine intermediate with two chlorine atoms and one remaining hydroxyl group, then utilizes the substitution reaction between the amino groups in p-aminodiphenylamine and 3,5-di-tert-butyl-4-hydroxybenzylamine and the two chlorine atoms to obtain a monohydroxy s-triazine derivative, and finally utilizes isophorone diisocyanate as a bridging agent to perform nucleophilic addition reactions with the hydroxyl groups in the monohydroxy s-triazine derivative and hydroxyethyl acrylate to obtain the modified hydroxyethyl acrylate.

[0017] The application utilizes acrylate soft monomers, acrylate hard monomers, modified hydroxyethyl acrylate, and acrylic acid as comonomers to prepare the modified acrylic resin through free radical polymerization under the action of an initiator. The modified hydroxyethyl acrylate has a s-triazine ring structure with good thermal stability and flame retardation effect, a benzene ring structure, and good hydrophobicity. The introduction of the amine-based anti-aging agent p-aminodiphenylamine and the hindered phenol antioxidant 3,5-di-tert-butyl-4-hydroxybenzylamine synergistically plays a role in high-temperature aging resistance, and the tack-reducing adhesive composition has good thermal stability, water resistance, high-temperature aging resistance, and flame retardation effect.

[0018] The present application grafts low molecular weight vinyl silicone oil in the middle of modified acrylate resin synthesis by way of hydrosilylation to form an acrylic-silicone block structure, significantly improving the heat resistance and weather resistance of the tack reducing adhesive composition, improving the adhesion in a humid heat environment, while avoiding the problem of silicone oil precipitation, in the tack reducing adhesive composition compounding process, the hydroxyl groups in the HDI trimer and the hydroxyl groups in the hydroxyl-terminated polybutadiene react to form a polyurethane-acrylic interpenetrating network, inhibiting the migration of ionic liquid, and further improving the temperature impact resistance of the adhesive film, while the introduction of silicone and hydroxyl-terminated polybutadiene can improve the ability of the tack reducing adhesive composition to remain debonded after high temperature and high humidity and cold and hot impact aging. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of the present application.

[0020] The preparation method of the modified hydroxyethyl acrylate in Example 1 includes the following steps: (1) 9.2 g of cyanuric chloride and 120 mL of chlorobenzene were added to a reactor, and after stirring and mixing, 10 g of anhydrous aluminum chloride was added in batches under ice water bath, and after stirring and mixing, 5.3 g of m-xylene was added dropwise, and the reaction was maintained for 2 h under ice bath, and after the reaction was completed, 100 mL of 2% hydrochloric acid was added dropwise to the reactor at room temperature, the organic layer was separated, the water layer was extracted with 100 mL of chlorobenzene, the combined organic layer was dried with anhydrous sodium sulfate, and after rotary evaporation under vacuum, filtration was performed to prepare a s-triazine intermediate; (2) 12.2 g of the s-triazine intermediate and 150 mL of chlorobenzene were added to a reactor, and after stirring and mixing, 6.4 g of anhydrous aluminum chloride was added in batches under ice water bath, and after stirring and mixing, 5.8 g of resorcinol was added, and the reaction was carried out at 80°C for 2 h, and after the reaction was completed, 150 mL of 2% hydrochloric acid was added dropwise to the reactor, and the chlorobenzene-water azeotrope was recovered by normal pressure distillation until the top temperature reached 100°C, and then hot filtration was performed, and the crude product was recrystallized with toluene to prepare a dihydroxyl-containing chloro-s-triazine intermediate; (3) 16.3 g of the dihydroxyl-containing chloro-s-triazine intermediate, 8.8 g of 1,4-p-dichlorobenzene and 150 mL of tetrahydrofuran were added to a reactor, and after stirring and mixing, the reaction was carried out under stirring at 70°C, 5.1 g of triethylamine was added in batches during the reaction, the reaction was carried out for 4 h, and after the reaction was completed, filtration, rotary evaporation and drying were performed to prepare a monohydroxyl-substituted chloro-s-triazine intermediate; (4) 14.1 g of monohydroxy-substituted chlorine-containing s-triazine intermediate and 150 mL of m-xylene were added to a reactor, stirred uniformly under ice water bath, then 5.6 g of p-aminodiphenylamine and 7.2 g of 3,5-di-tert-butyl-4-hydroxybenzylamine were added and stirred for 2 h, then warmed to 50°C, 2.4 g of sodium hydroxide was added, and stirring was continued for 6 h. After the reaction was completed, the monohydroxy s-triazine derivative was prepared by washing, filtering, and drying; (5) 16.2 g of the monohydroxy s-triazine derivative and 4.5 g of isophorone diisocyanate were added to a reactor, stirred and mixed, then 0.02 g of dibutyltin dilaurate was added, and stirring was continued at 40°C for 2 h. Then 2.5 g of hydroxyethyl acrylate was added, and stirring was continued at 50°C for 2 h. After the reaction was completed, the modified hydroxyethyl acrylate was prepared by filtration, rotary evaporation, and drying.

[0021] Example 2 A modified acrylic resin includes the following components by weight: 60 parts of butyl acrylate, 15 parts of methyl methacrylate, 6 parts of the modified hydroxyethyl acrylate prepared in Example 1, 2 parts of acrylic acid, 8 parts of vinyl silicone oil (molecular weight 500), 0.3 parts of initiator azobisisobutyronitrile, 0.08 parts of platinum catalyst, 41.5 parts of toluene, and 18 parts of ethyl acetate. The preparation method includes the following steps: S1, the components were weighed by weight parts. 30 parts of butyl acrylate, 7.5 parts of methyl methacrylate, 3 parts of modified hydroxyethyl acrylate, 1 part of acrylic acid, 21 parts of toluene, and 9 parts of ethyl acetate were taken in a reaction kettle, and preheating was carried out at 60°C for 0.5 h. S2, the reaction kettle was warmed to 70°C. In addition, 30 parts of butyl acrylate, 7.5 parts of methyl methacrylate, 3 parts of modified hydroxyethyl acrylate, 1 part of acrylic acid, 10.5 parts of toluene, 4.5 parts of ethyl acetate, and 0.15 parts of initiator azobisisobutyronitrile were added to a metering tank, and the dropping was completed within 3 h. S3, after the dropping was completed, the temperature was kept for 1 h, then 0.08 parts of platinum catalyst, 8 parts of vinyl silicone oil (molecular weight 500), and 10 parts of toluene were added to the metering tank, and the dropping was completed within 1 h. The temperature was kept for 1 h, then 0.15 parts of initiator azobisisobutyronitrile and 4.5 parts of ethyl acetate were added, and the dropping was completed within 0.5 h. After the temperature was kept for 2 h, the temperature was lowered, and the modified acrylic resin was discharged.

[0022] Example 3 An anti-aging tack-reducing adhesive composition includes the following components by weight: 60 parts of the modified acrylic resin prepared in Example 2, 10 parts of terpene phenolic resin, 8 parts of ionic liquid 1-aminopropyl-3-methyl imidazolium bis(trifluoromethylsulfonyl) imide salt, 5 parts of ionic channel additive PEG300, 1 part of HDI trimer, 15 parts of hydroxyl-terminated polybutadiene (molecular weight 1000), and 40 parts of ethyl acetate.

[0023] A preparation method of an electrically conductive tack-reducing adhesive tape includes the following steps: According to the above weight parts, each component is weighed, the modified acrylic resin, terpene phenolic resin, ionic liquid 1-aminopropyl-3-methyl imidazole bis(trifluoromethylsulfonyl) imidate salt, ionic channel additive PEG300, HDI trimer, hydroxyl-terminated polybutadiene, ethyl acetate are stirred at a speed of 300 r / min for 30 min, coated on the aluminum foil surface of the composite aluminum foil substrate in a coating manner, the dry adhesive thickness is 50 um, baked at 130℃ for 3 min, and then bonded with a 10g silicone release film to obtain the electrically conductive tack-reducing adhesive tape.

[0024] Example 4 An anti-aging tack-reducing adhesive composition includes the following components by weight: modified acrylic resin prepared in Example 2 65 parts, terpene phenolic resin 14 parts, ionic liquid 1-aminopropyl-3-methyl imidazole bis(trifluoromethylsulfonyl) imidate salt 10 parts, ionic channel additive PEG300 4 parts, HDI trimer 2 parts, hydroxyl-terminated polybutadiene (molecular weight 1000) 17 parts, ethyl acetate 60 parts.

[0025] A preparation method of an electrically conductive tack-reducing adhesive tape is the same as that in Example 3.

[0026] Example 5 An anti-aging tack-reducing adhesive composition includes the following components by weight: modified acrylic resin prepared in Example 2 70 parts, terpene phenolic resin 18 parts, ionic liquid 1-aminopropyl-3-methyl imidazole bis(trifluoromethylsulfonyl) imidate salt 13 parts, ionic channel additive PEG300 5.5 parts, HDI trimer 2.7 parts, hydroxyl-terminated polybutadiene (molecular weight 1000) 19 parts, ethyl acetate 76 parts.

[0027] A preparation method of an electrically conductive tack-reducing adhesive tape is the same as that in Example 3.

[0028] Comparative Example 1 A preparation method of a modified hydroxyethyl acrylate includes the following steps: (1) 9.2 g of cyanuric chloride and 120 mL of chlorobenzene were added to a reactor, stirred and mixed, then 10 g of anhydrous aluminum chloride was added in batches under ice water bath, stirred and mixed, then 5.3 g of m-xylene was added dropwise under ice bath, reacted for 2 h, after the reaction was completed, 100 mL of 2% hydrochloric acid was added dropwise into the reactor at room temperature, the organic layer was separated, the water layer was extracted with 100 mL of chlorobenzene, the combined organic layer was dried with anhydrous sodium sulfate, rotary evaporated under vacuum, and then filtered to prepare a s-triazine intermediate; (2) into the reactor 12.2 g of triazine intermediates and 150 mL of chlorobenzene, after stirring mixed in ice water bath under the batch addition of 6.4 g of anhydrous aluminum chloride, keep ice bath stirring mixed after adding 5.8 g of resorcinol, placed in 80 ℃ for 2 h, after the completion of the reaction to the reactor drop 150 mL of 2% hydrochloric acid, normal pressure distillation recovery chlorobenzene water azeotrope, to the top temperature 100 ℃ stop, hot filter, crude product with toluene recrystallization, preparation of double hydroxyl chlorine-containing triazine intermediates; (3) into the reactor 6.5 g of double hydroxyl chlorine-containing triazine intermediates and 4.5 g of isophorone diisocyanate, after stirring mixed in 0.02 g of dibutyltin dilaurate, placed in 40 ℃ for 2 h, then add 2.5 g of hydroxyethyl acrylate, placed in 50 ℃ continue to stir for 2 h, after the completion of the reaction by filter, rotary evaporation, drying, preparation of modified hydroxyethyl acrylate.

[0029] Comparative Example 2 A modified acrylic resin comprising the following components by weight: butyl acrylate 60 parts, methyl methacrylate 15 parts, modified hydroxyethyl acrylate prepared in Comparative Example 1 6 parts, acrylic acid 2 parts, vinyl silicone oil (molecular weight 500) 8 parts, initiator azobisisobutyronitrile 0.3 parts, platinum catalyst 0.08 parts, toluene 41.5 parts, ethyl acetate 18 parts; The preparation method comprises the following steps: S1, the components are weighed by weight parts, take butyl acrylate 30 parts, methyl methacrylate 7.5 parts, modified hydroxyethyl acrylate 3 parts, acrylic acid 1 part, toluene 21 parts, ethyl acetate 9 parts in the reaction kettle, placed in 60 ℃ for 0.5 h of preheating stirring; S2, the reaction kettle is heated to 70 ℃, and then take butyl acrylate 30 parts, methyl methacrylate 7.5 parts, modified hydroxyethyl acrylate 3 parts, acrylic acid 1 part, toluene 10.5 parts, ethyl acetate 4.5 parts and initiator azobisisobutyronitrile 0.15 parts are added to the metering tank, and the dropwise addition is completed within 3 h; S3, after the dropwise addition is completed, keep warm for 1 h, then add platinum catalyst 0.08 parts, vinyl silicone oil (molecular weight 500) 8 parts and toluene 10 parts to the metering tank, dropwise addition is completed within 1 h, keep warm for 1 h, then add initiator azobisisobutyronitrile 0.15 parts and ethyl acetate 4.5 parts, dropwise addition is completed within 0.5 h, keep warm for 2 h, then cool down and discharge, to prepare a modified acrylic resin.

[0030] Comparative Example 3 A modified acrylic resin comprising the following components by weight: butyl acrylate 60 parts, methyl methacrylate 15 parts, hydroxyethyl acrylate 6 parts, acrylic acid 2 parts, vinyl silicone oil (molecular weight 500) 8 parts, initiator azobisisobutyronitrile 0.3 parts, platinum catalyst 0.08 parts, toluene 41.5 parts, ethyl acetate 18 parts; The preparation method comprises the following steps: S1, weigh the components by parts by weight, take butyl acrylate 30 parts, methyl methacrylate 7.5 parts, hydroxyethyl acrylate 3 parts, acrylic acid 1 part, toluene 21 parts, ethyl acetate 9 parts in the reaction kettle, preheat under stirring at 60℃ for 0.5h; S2, the reaction kettle is heated to 70℃, and then butyl acrylate 30 parts, methyl methacrylate 7.5 parts, hydroxyethyl acrylate 3 parts, acrylic acid 1 part, toluene 10.5 parts, ethyl acetate 4.5 parts and initiator azobisisobutyronitrile 0.15 parts are added to the metering tank, and the dropping is completed within 3h; S3, after the completion of dropping, keep warm for 1h, then add platinum catalyst 0.08 parts, vinyl silicone oil (molecular weight 500) 8 parts and toluene 10 parts to the metering tank, drop within 1h, keep warm for 1h, then add initiator azobisisobutyronitrile 0.15 parts and ethyl acetate 4.5 parts, drop within 0.5h, keep warm for 2h, then cool down and discharge, to prepare the modified acrylic resin.

[0031] Comparative Example 4 A modified acrylic resin includes the following components by weight: butyl acrylate 60 parts, methyl methacrylate 15 parts, hydroxyethyl acrylate 6 parts, acrylic acid 2 parts, initiator azobisisobutyronitrile 0.55 parts, toluene 41.5 parts, ethyl acetate 18 parts; The preparation method includes the following steps: S1, weigh the components by parts by weight, take butyl acrylate 30 parts, methyl methacrylate 7.5 parts, hydroxyethyl acrylate 3 parts, acrylic acid 1 part, toluene 21 parts, ethyl acetate 9 parts in the reaction kettle, preheat under stirring at 60℃ for 0.5h; S2, the reaction kettle is heated to 70℃, and then butyl acrylate 30 parts, methyl methacrylate 7.5 parts, hydroxyethyl acrylate 3 parts, acrylic acid 1 part, toluene 10.5 parts, ethyl acetate 4.5 parts and initiator azobisisobutyronitrile 0.15 parts are added to the metering tank, and the dropping is completed within 3h; S3, after the completion of dropping, keep warm for 1h, then add platinum catalyst 0.08 parts, vinyl silicone oil (molecular weight 500) 8 parts and toluene 10 parts to the metering tank, drop within 1h, keep warm for 1h, then add initiator azobisisobutyronitrile 0.15 parts and ethyl acetate 4.5 parts, drop within 0.5h, keep warm for 2h, then cool down and discharge, to prepare the modified acrylic resin.

[0032] Comparative Example 5 An anti-aging tack-reducing adhesive composition includes the following components by weight: modified acrylic resin prepared in Comparative Example 2 60 parts, terpene phenolic resin 10 parts, ionic liquid 1-aminopropyl-3-methyl imidazole bis(trifluoromethylsulfonyl) imidazolium salt 8 parts, ionic channeling agent PEG300 5 parts, HDI trimer 1 part, hydroxyl-terminated polybutadiene (molecular weight 1000) 15 parts, ethyl acetate 40 parts.

[0033] A method for preparing an electrically conductive tack-reducing adhesive tape is the same as that of Example 3.

[0034] Comparative Example 6 An anti-aging tack-reducing adhesive composition comprises the following components in parts by weight: the modified acrylic resin prepared in Comparative Example 3 60 parts, terpene phenol resin 10 parts, ionic liquid 1-aminopropyl-3-methyl imidazolium bis(trifluoromethylsulfonyl) imide salt 8 parts, ionic channeling aid PEG300 5 parts, HDI trimer 1 part, hydroxyl-terminated polybutadiene (molecular weight 1000) 15 parts, ethyl acetate 40 parts.

[0035] A method for preparing an electrically conductive tack-reducing adhesive tape is the same as that of Example 3.

[0036] Comparative Example 7 An anti-aging tack-reducing adhesive composition comprises the following components in parts by weight: the modified acrylic resin prepared in Comparative Example 4 60 parts, terpene phenol resin 10 parts, ionic liquid 1-aminopropyl-3-methyl imidazolium bis(trifluoromethylsulfonyl) imide salt 8 parts, ionic channeling aid PEG300 5 parts, HDI trimer 1 part, hydroxyl-terminated polybutadiene (molecular weight 1000) 15 parts, ethyl acetate 40 parts.

[0037] A method for preparing an electrically conductive tack-reducing adhesive tape is the same as that of Example 3.

[0038] Comparative Example 8 An anti-aging tack-reducing adhesive composition comprises the following components in parts by weight: the modified acrylic resin prepared in Example 2 60 parts, terpene phenol resin 10 parts, ionic liquid 1-aminopropyl-3-methyl imidazolium bis(trifluoromethylsulfonyl) imide salt 8 parts, ionic channeling aid PEG300 5 parts, HDI trimer 1 part, ethyl acetate 40 parts.

[0039] A method for preparing an electrically conductive tack-reducing adhesive tape is the same as that of Example 3.

[0040] Performance detection The electrically conductive tack-reducing adhesive tapes prepared in Examples 3-5 and Comparative Examples 5-8 are subjected to performance detection: (1) Flame-retardant performance test: the flame-retardant performance of the sample is evaluated by limiting oxygen index, and the sample size is 125 mm x 12 mm x 3 mm. Generally, the larger the limiting oxygen index, the better the flame-retardant performance, and vice versa. The data results are shown in Table 1.

[0041] Table 1 Results of flame-retardant performance detection of samples ; From the data results in Table 1, it can be seen that the power-on adhesion-reducing adhesive tapes prepared in Examples 3-5 have good flame retardant properties. Among them, the modified acrylic resin added in Comparative Examples 6-7 is not modified with hydroxyethyl acrylate, and the limiting oxygen index of Comparative Examples 6-7 is lower than that of Examples 3-5, because the triazine ring structure introduced in the modified hydroxyethyl acrylate has good thermal stability and flame retardant effect.

[0042] (2) According to GB / T 2792-2014 "Test method for adhesive tape peel strength", the peel strength of the power-on adhesion-reducing adhesive tape before and after power-on is tested under cold-heat shock (-40℃~70℃, 24h), high temperature and high humidity (60℃, 95% humidity, 144h) conditions, and the steel plate surface residual glue test is carried out, and the data results are shown in Tables 2-3.

[0043] Table 2: Sample cold-heat shock resistance test results ; From the data results in Table 2, it can be seen that the power-on adhesion-reducing adhesive tapes prepared in Examples 3-5 still have high adhesion before power-on and ultra-low adhesion after power-on after cold-heat shock, can be firmly adhered to the substrate and easily peeled off after power-on, and no residual glue occurs. Among them, the modified acrylic resin added in Comparative Example 5 is not grafted with amine antioxidant and hindered phenolic antioxidant, the modified acrylic resin added in Comparative Example 6 is not modified with hydroxyethyl acrylate, the modified acrylic resin added in Comparative Example 7 is not modified with hydroxyethyl acrylate and not grafted with vinyl silicone oil, and no hydroxyl-terminated polybutadiene is introduced in Comparative Example 8. The adhesion of Comparative Examples 5-8 before power-on under cold-heat shock is lower than that of Examples 3-5, the power consumption is larger than that of Examples 3-5, the temperature stability is poorer than that of Examples 3-5, and residual glue occurs, because the introduction of amine antioxidant, hindered phenolic antioxidant and triazine ring structure improves the heat resistance of the material, and the introduction of vinyl silicone oil and hydroxyl-terminated polybutadiene improves the temperature impact resistance of the material.

[0044] Table 3: Sample high temperature and high humidity resistance test results ; From the data results in Table 3, it can be seen that the power-on adhesion-reducing adhesive tapes prepared in Examples 3-5 still have high adhesion before power-on and ultra-low adhesion after power-on, can firmly adhere to the substrate and easily peel off after power-on, and do not have the phenomenon of residual glue. The adhesion of the comparative examples 5-8 before power-on is lower than that of Examples 3-5, the power consumption is greater than that of Examples 3-5, the stability is poorer than that of Examples 3-5, and the phenomenon of residual glue occurs. The reason is that the introduction of amine antioxidant, hindered phenol antioxidant, triazine ring structure and benzene ring structure improves the high temperature resistance and water resistance of the material, and the introduction of vinyl silicone oil and hydroxyl-terminated polybutadiene enables the material to maintain the ability to debond after high temperature and humidity aging.

[0045] In the description of the present specification, the description referring to the terms "one embodiment", "an example", "a specific example" and the like means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0046] The basic principles, main features and advantages of the present application are shown and described above. It should be understood by those skilled in the art that the present application is not limited by the above examples, and the above examples and descriptions in the specification are only to illustrate the principles of the present application. Without departing from the spirit and scope of the present application, various changes and improvements can be made to the present application, and these changes and improvements all fall within the scope of the claimed present application.

Claims

1. An age resistant tack-reducing adhesive composition characterized in that, The modified acrylic resin comprises the following components by weight: 60-75 parts of modified acrylic resin, 10-20 parts of tackifying resin, 8-15 parts of ionic liquid, 3-6 parts of ion channeling agent, 1-3 parts of HDI trimer, 15-20 parts of hydroxyl-terminated polybutadiene, and 40-80 parts of ethyl acetate; The modified acrylic resin comprises the following components by weight: 40-70 parts of acrylic ester soft monomer, 10-20 parts of acrylic ester hard monomer, 5-10 parts of modified hydroxyethyl acrylate, 2-8 parts of acrylic acid, 5-10 parts of vinyl silicone oil, 0.2-1 part of initiator, 0.05-0.1 part of platinum catalyst, and 50-60 parts of solvent; The modified hydroxyethyl acrylate is prepared by using isophorone diisocyanate as a bridging agent to respectively react with a monohydroxy-s-triazine derivative and hydroxyethyl acrylate through nucleophilic addition reaction; The monohydroxy-s-triazine derivative is prepared by using cyanuric chloride and m-xylene to synthesize a s-triazine intermediate through a Friedel-Crafts reaction, then performing a Friedel-Crafts reaction on the s-triazine intermediate and resorcinol to obtain a dihydroxy-s-triazine intermediate containing chlorine, then performing a substitution reaction on the dihydroxy-s-triazine intermediate containing chlorine and 1,4-p-dichlorobenzyl to obtain a monohydroxy-s-triazine intermediate containing chlorine, and then performing a substitution reaction on the monohydroxy-s-triazine intermediate containing chlorine and p-aminodiphenylamine and 3,5-di-tert-butyl-4-hydroxybenzylamine.

2. The age resistant tack reducing glue composition according to claim 1, characterized in that, The preparation method of the modified acrylic resin comprises the following steps: S1, the components are weighed by weight parts, the acrylic ester soft monomer, the acrylic ester hard monomer, the modified hydroxyethyl acrylate, the acrylic acid and the solvent are taken into a reaction kettle, and preheating is performed under stirring at 55-65℃ for 0.5-1h; S2, the reaction kettle is heated to 70-75℃, the acrylic ester soft monomer, the acrylic ester hard monomer, the modified hydroxyethyl acrylate, the acrylic acid, the solvent and the initiator are taken into a metering tank, and the dropping is completed within 3h; S3, after the dropping is completed, the temperature is kept for 0.5-1h, then the platinum catalyst, the vinyl silicone oil and the solvent are added to the metering tank, the dropping is completed within 1h, the temperature is kept for 1-1.5h, then the initiator and the solvent are added, the dropping is completed within 0.5h, the temperature is kept for 1.5-2h, then the temperature is lowered to discharge the product, and the modified acrylic resin is prepared.

3. The age resistant tack reducing glue composition according to claim 2, wherein The preparation method of the modified hydroxyethyl acrylate comprises the following steps: (1) the cyanuric chloride and chlorobenzene are added into a reactor, after stirring and mixing, anhydrous aluminum chloride is added in batches under ice water bath, m-xylene is added dropwise under ice water bath, the reaction is kept for 2-3h, after the reaction is completed, hydrochloric acid is added dropwise into the reactor at room temperature, the organic layer is separated, the water layer is extracted with chlorobenzene, the combined organic layer is dried with anhydrous sodium sulfate, rotary evaporation is performed under vacuum, and then filtration is performed, and the s-triazine intermediate is prepared; (2) the s-triazine intermediate and chlorobenzene are added into a reactor, after stirring and mixing, anhydrous aluminum chloride is added in batches under ice water bath, m-xylene is added dropwise under ice water bath, the reaction is kept for 2-3h, after the reaction is completed, hydrochloric acid is added dropwise into the reactor, chlorobenzene-water azeotrope is recovered through normal pressure distillation until the top temperature reaches 100℃, hot filtration is performed, and the crude product is recrystallized with toluene, and the dihydroxy-s-triazine intermediate containing chlorine is prepared; (3) adding a dihydroxy chlorine-containing s-triazine intermediate, 1,4-p-dichlorobenzene and tetrahydrofuran into the reactor, stirring and mixing, and then stirring and reacting at 65-75°C, adding triethylamine in batches during the reaction, and then stopping the reaction after 4-5h, and then preparing a monohydroxy-substituted chlorine-containing s-triazine intermediate by filtration, rotary evaporation and drying; (4) adding the monohydroxy-substituted chlorine-containing s-triazine intermediate and m-xylene into the reactor, stirring uniformly in an ice water bath, then adding p-aminodiphenylamine and 3,5-di-tert-butyl-4-hydroxybenzylamine, stirring and reacting for 1-2h, then increasing the temperature to 40-60°C, adding sodium hydroxide, and continuing to stir and react for 5-7h, and then preparing a monohydroxy s-triazine derivative by washing, filtering and drying after the reaction is completed; (5) adding the monohydroxy s-triazine derivative and isophorone diisocyanate into the reactor, stirring and mixing, then adding dibutyltin dilaurate, stirring and reacting at 35-45°C for 1-2h, then adding hydroxyethyl acrylate, and continuing to stir and react at 45-55°C for 1-2h, and then preparing modified hydroxyethyl acrylate by filtration, rotary evaporation and drying after the reaction is completed.

4. The age resistant tack reducing glue composition according to claim 3, characterized in that, The molar ratio of cyanuric chloride to m-xylene in step (1) is 1:1-1.1; and the molar ratio of the s-triazine intermediate to resorcinol in step (2) is 1:1-1.

1.

5. The age resistant tack reducing glue composition of claim 3, wherein, The molar ratio of the dihydroxy chlorine-containing s-triazine intermediate to 1,4-p-dichlorobenzene in step (3) is 1:1-1.1; and the molar ratio of the monohydroxy-substituted chlorine-containing s-triazine intermediate, p-aminodiphenylamine and 3,5-di-tert-butyl-4-hydroxybenzylamine in step (4) is 1:1-1.1:1-1.

1.

6. The age resistant tack reducing glue composition of claim 3, wherein, The molar ratio of the monohydroxy s-triazine derivative, isophorone diisocyanate and hydroxyethyl acrylate in step (5) is 1:1-1.1:1-1.

2.

7. The age resistant tack reducing glue composition of claim 1, wherein, The acrylic ester soft monomer includes at least one of ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, lauryl acrylate and stearyl acrylate; and the acrylic ester hard monomer includes at least one of methyl methacrylate, tert-butyl acrylate and cyclohexyl acrylate.

8. The age resistant tack reducing glue composition of claim 1, wherein, The molecular weight of the vinyl silicone oil is 500-1000; the Pt concentration in the platinum catalyst is 3000ppm; the initiator is at least one of azobisisobutyronitrile and dibenzoyl peroxide; and the solvent is a mixed solvent of toluene and ethyl acetate.

9. The age resistant tack reducing glue composition of claim 1, wherein, The tackifying resin is at least one of terpene resin, terpene phenolic resin, hydrogenated terpene resin, C5 / C9 petroleum resin and rosin resin; the ionic liquid is at least one of imidazole, pyridine, quaternary ammonium, quaternary phosphonium, pyrrolidine and piperidine; and the ionic channel additive is at least one of low-molecular-weight polyethylene glycol, γ-butyrolactone, 1,3-dioxolane, N-methylpyrrolidone and propylene glycol methyl ether.

10. Use of the age resistant tack reducing adhesive composition according to claim 1 in an electrically conductive adhesive tape, characterized in that, The application The method comprises the following steps: weighing each component by weight parts, stirring and mixing the modified acrylic resin, tackifying resin, ionic liquid, ion channeling agent, HDI trimer, hydroxyl-terminated polybutadiene and ethyl acetate uniformly, coating the aluminum foil surface of the composite aluminum foil substrate in a coating manner, drying, and then pasting a silicone release film to obtain a power-on adhesion-reducing adhesive tape.